2018
DOI: 10.1016/j.conctc.2018.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Temperament and character in men with autism spectrum disorder: A reanalysis of scores on the Temperament and Character Inventory by individual case matching

Abstract: BackgroundInterest in autism spectrum disorders (ASD) in adulthood is increasing. Although a person may be diagnosed with ASD, the diagnosis reveals little about the individual's temperament, character, and personality. Also, relatively little is known about the personality of adults with ASD.MethodA reanalysis of scores on the Temperament and Character Inventory (TCI) administered to a group of 66 normally intelligent men aged 18–63 years, diagnosed with ASD, by individual case matching to a comparison group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…Individuals with ASD are characterized by defects in social communication and repetitive and stereotyped behaviours 56 . In addition, they present a wide range of symptoms such as defects in motor coordination, altered sensory processing, novelty seeking and decreased cognitive flexibility 5761 . We measured sensory perception/novelty detection using the texture novel object recognition paradigm (tNORT 62 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Individuals with ASD are characterized by defects in social communication and repetitive and stereotyped behaviours 56 . In addition, they present a wide range of symptoms such as defects in motor coordination, altered sensory processing, novelty seeking and decreased cognitive flexibility 5761 . We measured sensory perception/novelty detection using the texture novel object recognition paradigm (tNORT 62 ).…”
Section: Resultsmentioning
confidence: 99%
“…Autism spectrum disorders are a complex group of disorders characterized by social deficits, language impairment and repetitive behaviours. However, patients with ASD also present abnormal sensory processing 58 , novelty seeking 61 , working memory 71 , cognitive flexibility 59 and sensorimotor gating 72 . Some of these phenotypes have also been associated with schizophrenia 64,65 .…”
Section: Discussionmentioning
confidence: 99%
“…Studies using the temperament and character inventory (TCI) to evaluate personality in patients with ASD are presented in Table 4 [ 48 ]. Four TCI studies on adults with ASD[ 47 , 49 - 51 ] found low scores on the character dimensions of self-directedness and cooperativeness. Moreover, ASD was associated with high harm avoidance, low reward dependence, low novelty seeking and high self-transcendence.…”
Section: Resultsmentioning
confidence: 99%
“…Vuijk et al [ 51 ] performed a re-analysis of scores on the TCI administered to a sample of 66 ASD men by individual case matching. Compared to the general population, patients with ASD scored significantly higher on the scale for harm avoidance, and lower on novelty seeking, reward dependence, self-directedness, and cooperativeness.…”
Section: Resultsmentioning
confidence: 99%
“…of reward). Studies have shown lower reward dependence scores for men with ASD (Vuijk et al, 2018), indicative of being rational and perhaps independent from sentimental considerations. This could possibly be linked to difficulties in understanding others emotions and beliefs (ToM).…”
Section: Temperament and Character Inventory (Reward Dependence Subscale)mentioning
confidence: 99%